Quantitative assessment of the financial sector : an integrated approach - Worrell, DeLisle ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2004)
Suggests a strategy designed to make best use of the available quantitative techniques of financial sector assessment.